Correlation between Plasma Levels of RIP3 and Acute Ischemic Stroke with Large-Artery Atherosclerosis - Chen, Beilei; Hang, Jing; Zhao, Yuanyuan; Geng, Yang; Li, Xiaobo; Gu, Zhie; Li, Jun; Jiang, Chao; Tao, Luhang; Yu, Hailong (Current neurovascular research, 2022)
Receptor-interacting serine-threonine protein kinase 3 (RIP3) was previously discovered to be an important medium in the occurrence and development of major atherosclerotic cerebral infarction. However, the role of RIP3 in acute ischemic stroke remains unclear. This study aimed to explore the correlation between plasma levels of RIP3 and acute ischemic stroke with large-artery atherosclerosis (LAA). This prospective study enrolled 116 patients with LAA, 40 healthy controls and 30 acute ischemic stroke patients with small-artery occlusion. The patients with LAA were divided according to the quartile of plasma levels of RIP3. Logistic regression model was used for comparison. The ROC curve was performed to evaluate the predictive value. In patients with LAA, the RIP3 levels in patients with poor outcomes as well as neurological deterioration were significantly higher than those with good outcomes (P < 0.001) and without neurological deterioration (P = 0.014) respectively. Patients in the highest levels of plasma RIP3 quartile were more likely to have neurological deterioration (OR, 11.07; 95% CI, 1.990-61.582) and poor outcomes (OR, 35.970; 95% CI, 5.392-239.980) compared with the lowest. The optimal cut-off value for neurological deterioration was 1127.75 pg/mL (specificity, 66.7%; sensitivity, 69.2%), that for poor prognosis was 1181.82 pg/mL (specificity, 89.7%; sensitivity, 62.1%). Elevated levels of plasma RIP3 were significantly associated with neurological deterioration and poor prognosis in patients with LAA. Significant increase in plasma RIP3 levels can predict neurological deterioration and poor prognosis of these patients.